Research on the knowledge representation and retrieval for mechanical product design based on ontology. (30th May 2019) - Su, Shaohui; Wang, Yiting; Chen, Chang; Li, Pengfei; Zhang, Dongyang; Chen, Guojin
Different subjects are applied in the design of mechanical products. For efficient sharing and reusing of knowledge in the diverse forms of information, this study presents the classification of mechanical design and the process of ontology construction. The knowledge of mechanical field can fully express the semantics and syntax of concept through the function of ontology. Furthermore, based on the representation of ontology knowledge, it establishes a knowledge retrieval model of mechanical products and proposes a corresponding retrieval algorithm, which implements much higher precision and recall in the mechanical field.